2010
DOI: 10.1093/aje/kwq004
|View full text |Cite
|
Sign up to set email alerts
|

The Association Between Atopy and Childhood/Adolescent Leukemia: A Meta-Analysis

Abstract: Atopic disease is hypothesized to be protective against several malignancies, including childhood/adolescent leukemia. To summarize the available epidemiologic evidence, the authors performed a meta-analysis of associations between atopy/allergies, asthma, eczema, hay fever, and hives and childhood/adolescent leukemia, acute lymphoblastic leukemia (ALL), and acute myeloid leukemia (AML). They searched MEDLINE literature (1952-March 2009) and queried international experts to identify eligible studies. Ten case-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
82
3
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 83 publications
(89 citation statements)
references
References 57 publications
2
82
3
1
Order By: Relevance
“…The association of atopy with cancer risk has been explored but only in limited studies [11,12,13,14]; however, a positive association between asthma and lung cancer has been confirmed. In contrast, there is some evidence that the immune systems of allergy patients can display anticancer activity, including significantly stronger NK cell activity against other cells (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…The association of atopy with cancer risk has been explored but only in limited studies [11,12,13,14]; however, a positive association between asthma and lung cancer has been confirmed. In contrast, there is some evidence that the immune systems of allergy patients can display anticancer activity, including significantly stronger NK cell activity against other cells (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…There have been several investigations regarding definition and measurement of allergies and the subtypes of HM assessed, however, an inverse association with history of allergies has been reported for HM as a group [4], lymphoma overall [5,6], Hodgkin's lymphoma (HL), Non Hodgkin lymphoma (NHL) [7][8][9][10], Acute Lymphoblastic Leukemia (ALL) [11,12], and multiple myeloma (MM) [13] (Table 1) [14]. The study indicates a moderately increased risk of HMs in women but not in men with a history of allergies to airborne allergens, especially to plants, grass, or trees.…”
Section: Allergy and Hematologic Malignanciesmentioning
confidence: 99%
“…The presence of an allergic condition could be a surrogate marker of increased vigilance of the immune system in scrutinizing, identifying, and destroying cancer cells [11].…”
Section: Allergy As Protective Factor: Possible Mechanismsmentioning
confidence: 99%
“…According to the cancer immune surveillance hypothesis, the immune system identifi�� ��� ���������� �b������ ����� �� ��� body, ��u� �v������ ��� ��v���p���� �� � �u�b�� �� p�������� malignancies (34). The occurrence of asthma may be a surro-���� ���k�� �� �� increased ability of ��� immune system �� recogniz� and destroy malignant cells (23). By contrast, ��� antigenic stimulation hypothesis �u������ ���� ��� ������� inflammatory state in asthma��� patients may result in an inflammatory cytokine cascade and lead to tissue damage ���, ultimately, lymphoid malignancies (35).…”
Section: Discussionmentioning
confidence: 99%
“…By contrast, ��� ��������� ����u������ hypothesis suggest� ���� ���u��-����u������ ���������� may p�����p��� �� ������, �u� �� �� ���������� �u�b�� �� ������ mutations in activated dividing immune cells (9)(10)(11)(12). P��v��u� ��u���� �u������� ���� ������ w�� p�������v� ������� ��uk���� and lymphoma (13)(14)(15)(16), whereas other studies indicated asthma �� a risk factor (17)(18)(19), or ��p����� no association (20)(21)(22)(23).…”
Section: Introductionunclassified